2003
DOI: 10.1046/j.1365-2958.2003.03765.x
|View full text |Cite
|
Sign up to set email alerts
|

The majority of inducible DNA repair genes in Mycobacterium tuberculosis are induced independently of RecA

Abstract: SummaryIn many species of bacteria most inducible DNA repair genes are regulated by LexA homologues and are dependent on RecA for induction. We have shown previously by analysing the induction of recA that two mechanisms for the induction of gene expression following DNA damage exist in Mycobacterium tuberculosis . Whereas one of these depends on RecA and LexA in the classical way, the other mechanism is independent of both of these proteins and induction occurs in the absence of RecA. Here we investigate the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
189
1
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(203 citation statements)
references
References 40 publications
8
189
1
5
Order By: Relevance
“…It is significant that uvrA and uvrB are induced in mycobacteria upon treatment with DNA-damaging agents like mitomycin C as well as upon infecting human macrophages (Rand et al, 2003;Graham & Clark-Curtiss, 1999). Thus, NER seems to be central to DNA repair mechanisms in mycobacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is significant that uvrA and uvrB are induced in mycobacteria upon treatment with DNA-damaging agents like mitomycin C as well as upon infecting human macrophages (Rand et al, 2003;Graham & Clark-Curtiss, 1999). Thus, NER seems to be central to DNA repair mechanisms in mycobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The genome sequences of M. tuberculosis (Cole et al, 1998), Mycobacterium leprae (Cole et al, 2001;Smith et al, 1997) and Mycobacterium smegmatis (http://www.tigr.org) have suggested that mismatch repair enzymes are missing in these organisms (Mizrahi & Andersen, 1998), and the role of RecA has been found to be minimal in mutation prevention (Boshoff et al, 2003;Rand et al, 2003). Thus, among the major DNA repair pathways, the base excision repair (BER) and the nucleotide excision repair (NER) pathways presumably contribute significantly to the maintenance of the genomic integrity in these bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…The genome sequences of Mycobacterium tuberculosis and Mycobacterium smegmatis have revealed that they lack the mismatch repair and the very short patch repair pathway enzymes (Cole et al, 1998;Mizrahi & Andersen, 1998). Furthermore, RecA-mediated repair also does not appear to play a significant role in mutation prevention in mycobacteria (Boshoff et al, 2003;Rand et al, 2003). Thus, the base-and nucleotide-excision repair pathways must play significant roles in maintaining genomic integrity in these bacteria (Kurthkoti et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…RecA elicits the SOS response upon binding single-stranded DNA and stimulating the autocleavage of LexA (3). RecA-inducible, LexArepressible genes have been extensively characterized in several bacterial species including B. subtilis (5)(6)(7)(8). In B. subtilis, cell division and development (sporulation) are regulated, in part, by a RecAdependent mechanism (4,9).…”
mentioning
confidence: 99%